2022
DOI: 10.1111/ijtd.12295
|View full text |Cite
|
Sign up to set email alerts
|

Training design enhancement through training evaluation: Effects on training transfer

Abstract: This research investigates the linkage between training evaluation, learning design and training transfer. A new training evaluation model, (i.e., learning‐transfer evaluation model [LTEM]), was used to examine its ability to provide evaluative evidence through robust assessments in pre‐, post‐ and delayed assessments. The model was used to improve the training design of a nursing training programme and to nudge the stakeholders to change their training practices. A mixed‐methods research approach, called conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…Technology provides an opportunity to enhance the educational experience, no matter in paths of facilitating the engagement, preservation, or realworld skill building if being applied judiciously alongside in-person teaching. Tomlinson et al (2020) and Arabi et al (2023) found that good planning improves job results for graduates. The studies show clear links between program design, knowledge application, and job market shifts.…”
Section: Assessing the Influence Of Program Design On Transfer Of Tra...mentioning
confidence: 99%
“…Technology provides an opportunity to enhance the educational experience, no matter in paths of facilitating the engagement, preservation, or realworld skill building if being applied judiciously alongside in-person teaching. Tomlinson et al (2020) and Arabi et al (2023) found that good planning improves job results for graduates. The studies show clear links between program design, knowledge application, and job market shifts.…”
Section: Assessing the Influence Of Program Design On Transfer Of Tra...mentioning
confidence: 99%
“…Moreover, nursing students often face stressful situations from the first moments of their professional education (Gürdil Yilmaz et al, 2022), including the intense level of stress typically associated with their first clinical experiences (Li et al, 2020) and resulting from their lack of professional knowledge and skills, perceptions of time pressure, and various coping difficulties (Uysal & Çalışkan, 2022). Furthermore, given the many challenges nurses face when carrying out their professional tasks, the smooth running of healthcare organizations is partly linked to the ability of nursing students to learn and quickly transfer the knowledge acquired during their training (Arabi & Garza, 2023). Unfortunately, although healthcare organizations consider training to be essential to the professional development of nurses and invest a great deal of money in this area, the problems associated with training transfer are real.…”
Section: Engagement Trajectoriesmentioning
confidence: 99%
“…A valid and reliable Feedback Quality Instrument(FQI) can provide educators and researchers with con dence that the feedback being assessed truly re ects the quality of the feedback given, which is essential for improving learning outcomes (5). For instance, feedback that is speci c, timely, and linked to learning objectives can signi cantly enhance student performance and self-regulation (10). Moreover, a supportive feedback environment can positively correlate with job satisfaction, leader-member exchange, and reduce psychological distress (9).…”
Section: Introductionmentioning
confidence: 99%